Mineralogical distinctions of carbonates in desert soils - Kraimer, R.A; Monger, H.C; Steiner, R.L (Soil Science Society of America journal, 2005)
Soil carbonate-C is a large pool of C and, in desert environments, is the dominant type of C stored in soil. To more fully understand the global C cycle and the role of soil in C sequestration, it is important to recognize how C enters and leaves the carbonate pool, as well as identify the forms of carbonate that exist in the soil. In the Desert Project in southern New Mexico, soils formed in limestone and igneous (mostly quartz monzonite and some rhyolite) parent materials lie adjacent to each other, with climate, vegetation, topography, age, and, to a large extent, dust deposition constant across the soils of both parent materials. The purpose of this study was to determine if X-ray diffractometry (XRD) can mineralogically identify the size fraction in which pedogenic carbonate occurs and discern differences among (i) pedogenic carbonate formed in limestone parent material, (ii) pedogenic carbonate formed in igneous parent material, and (iii) soil carbonate in the form of detrital limestone. The diffractograms revealed that the size fractions in which pedogenic carbonate occurs in a dolostone residuum are fine sand, silt, and clay. X-ray diffraction could not discern differences in soil carbonate because calcite was the only carbonate mineral present in the samples of pedogenic carbonate formed in limestone parent material, pedogenic carbonate formed in igneous parent material and detrital limestone. Excepting the d-spacing associated with a minor peak, statistical analysis found no significant differences in d-spacings among the three types of soil carbonate. However, each of the three types of soil carbonate revealed significant differences in d-spacings relative to those of the calcite reference. While XRD mineralogically revealed the size distribution of pedogenic carbonate formed in a dolostone residuum, for the purpose of C sequestration, XRD was unable to distinguish the three soil carbonate types.